2013
DOI: 10.1002/mma.2863
|View full text |Cite
|
Sign up to set email alerts
|

A unified discontinuous Galerkin framework for time integration

Abstract: We introduce a new discontinuous Galerkin approach for time integration. On the basis of the method of weighted residual, numerical quadratures are employed in the finite element time discretization to account for general nonlinear ordinary differential equations. Many different conditions, including explicit, implicit, and symplectic conditions, are enforced for the test functions in the variational analysis to obtain desirable features of the resulting time-stepping scheme. The proposed discontinuous Galerki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 46 publications
(208 reference statements)
0
10
0
Order By: Relevance
“…The case of low regularity is handled by our analysis. Our particular choice of Runge-Kutta methods is based on the known relationship between those time-stepping techniques and the discontinuous Galerkin in time method [2,3]. In other words, our proposed method is equivalent to a combined mixed finite element, discontinuous Galerkin method in space with a discontinuous Galerkin method in time.…”
Section: Introductionmentioning
confidence: 99%
“…The case of low regularity is handled by our analysis. Our particular choice of Runge-Kutta methods is based on the known relationship between those time-stepping techniques and the discontinuous Galerkin in time method [2,3]. In other words, our proposed method is equivalent to a combined mixed finite element, discontinuous Galerkin method in space with a discontinuous Galerkin method in time.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate the convergence behavior and performance of the GCC 2 (5) Galerkin-collocation approach, we present in Table 4 our numerical results for the test problem (26). The expected convergence of sixth order in time is nicely observed in all norms.…”
Section: Iterative Solver and Convergence Studymentioning
confidence: 97%
“…This leads to continuous or discontinuous approximations of the time variable (cf. e.g., [21,26]). Further, the fully coupled treatment of all time steps versus time-marching approaches is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper the authors showed that, for finite elements of order q, the method is strongly A-stable, has convergence order 2q + 1 in the nodes, and is equivalent to an implicit (RK) time stepper with q intermediate steps. The first analysis on DG methods as time stepping techniques was provided by [12] and [17], followed by the work of [41,50,48]. More recently, specialized solution methods have been introduced, for example by [45,40,31,4].…”
Section: Discontinuous Galerkinmentioning
confidence: 99%